SYSTEMATIC REVIEW AND META-ANALYSIS ON THE RELATIONSHIP BETWEEN NEURODEGENERATIVE BIOMARKERS AND NEUROBEHAVIORAL CHANGES - Ristinawati, Ira; Ilhamsyah, Rudi; Yang, Han; Pradana, Muhammad Yusuf Brilliant; Putra, Mohammad Sandhia Mahardhika (MNJ (Malang Neurology Journal), 2026)
Background: Neurodegenerative diseases represent a growing global health challenge, with early detection remaining elusive in clinical settings. Recent advances in fluid biomarkers have enabled the identification of molecular changes preceding clinical symptoms, thus offering promising avenues for early diagnosis and personalized management. This review synthesizes current findings on biomarker utility alongside neuroimaging in neurodegenerative disease detection and prognosis Objective: To evaluate the diagnostic accuracy and prognostic value of fluid biomarkers and neuroimaging in the early detection of neurodegenerative diseases, with a focus on Alzheimer’s disease. Methods: This systematic review and meta-analysis, registered in PROSPERO (CRD420251142436), followed PRISMA guidelines. Comprehensive searches across PubMed and Scopus identified peer-reviewed studies from 1985–2025 on neurodegenerative biomarkers and neurobehavioral changes. Standardized mean differences (SMD) along with 95% confidence intervals (CI) were calculated using a random-effects model to address study variability. The degree of heterogeneity was quantified by the I² statistic, while publication bias was assessed qualitatively due to the limited number of included studies. Results: This Meta-analysis reveals heterogeneity in biomarker-MRI correlations, biomarkers demonstrate remarkable accuracy in detecting Alzheimer’s at its earliest stages. This early detection capability for early intervention. No consistent overall effect emerged, underscoring standardization protocols remains a major challenge. Conclusion: Biomarker represent a promising approach for early detection and precise intervention in Alzheimer’s disease. Integrating fluid biomarkers, advanced neuroimaging, and standardized cerebrospinal fluid analysis enhances diagnostic accuracy and enables timely therapy during the prodromal stage. Future research should explore synergies between fluid biomarkers and digital cognitive tools to develop scalable, cost-effective screening protocols.